Implementation of article 67.1 of the Russian Constitution in the context of scientific historical and legal experience - M. A. Kozhevina (Правоприменение, 2021)
The subject of the research is the constitutional and legal norms of Article 67.1 of the Russian Constitution. These legal norms are legal means of realizing the subjective right to possess objectively verified knowledge about the past of the state and society and providing guarantees in obtaining such knowledge.The purpose of article is to confirm or disprove hypothesis that some historical facts have the potential of legalization and may be involved in the process of legal impact on public relations.The methodology. A systematic approach was used in combination with historical and logical methods of cognition. It made it possible to study the theoretical, factual and legal grounds for the implementation of Article 67.1 of the Russian Constitution. The formal legal method was also used. It determined the vector of analysis of the legal source and the internal structure of the legal norms of Article 67.1, as well as the legal and technical features of their implementation and enforcement.The main results, scope of application. The article stipulates a set of theoretical, factual and legal grounds for the implementation of Article 67.1 of the Russian Constitution. It is shown that the synthesis of scientific knowledge and historical memory, the object of which is the past of a person, society and the state, lies at the basis of legal practice. Such synthesis conttains the potential for the effective implementation of the subjective right to possess objectively verified knowledge of the past and create guarantees in obtaining such knowledge. Scientific historical and legal experience is defined as a necessary condition in achieving the goal of forming an individual and a citizen, resistant to ignorance and misunderstanding of his national identity, reveals its possibilities in substantiating and verifying a historical fact, as well as within the permissible limits of their legalization.Conclusions. Legal matter is systematic and is strictly organized, therefore it can neither be interpreted arbitrarily, nor applied unreasonably. Article 67.1 of Russian Constitution includes four parts, each of which determines the subsequent one. These parts are also in semantic connection with other constitutional principles and declarations, which together determine the mechanism of legal regulation of a special kind of social relations - relations to the past. The state as a subject of these relations, on the one hand, is the creator of conditions for a representative scientific search and the establishment of reliable historical facts, for the subsequent popularization of the scientific result. On the other hand, state legally fixes scientifically grounded facts of state and social development, indicating unity and continuity. Article 67.1 of the Russian Constitution represents an attempt to consolidate legally the well-established historical facts. A historical fact becomes a constant of historical heritage for society when it receives public recognition. The loss of such constant is an irreversible loss (possibly even the destruction of a part or a whole society). In this case historical fact can be defined as a historical truth and may become a subject to legalization, subsequently acquiring the status of a legal norm: principle, definitive, declarative, prescriptive or logical rule of law. The legal concept of historical truth should be perceived not as the opposite of historical untruth (lie), not in the sense of “this is good, but this is bad” and “who benefits from”, because emotionality goes beyond the legal framework. The legal concept of historical truth should be perceived as the opposite of an unscientific, hypothetically assumed, yet unproven historical fact.